Maternal serum and amniotic fluid CEA, CA125 and SCC patterns during pregnancy and labor - Sarandakou, A.; Kassanos, D.; Botsis, D.; Rizos, D.; Trakakis, E.; Phocas, I. (Clinical Chemistry and Enzymology Communications, 1998)
Maternal serum (MS) and amniotic fluid (AF) antigen concentrations were measured, by a microparticle EIA, in 28 pregnant women during the 2nd trimester, in 27 during the 3rd and in 34 during labor. Extremely elevated and scattered over a broad range antigen values were observed in AF, compared to those in MS samples (p < 0.0001). CEA values in both MS (100% < 5 ng/mL) and in AF did not differ significantly with advancing gestation, while CA125 in MS (6.5% > 32.5 U/mL) and in AF declined significantly with gestational age (p < 0.0001). In contrast SCC values in both MS (42.5% > 1.5 ng/mL) and in AF increased significantly with the progression of pregnancy (p < 0.0001). Amniotic fluid CA125 and less prominent SCC values were significantly higher in the 2nd trimester pregnancies, complicated by fetal anomalies, compared to those in normal pregnancies (p < 0.02 and p < 0.05 respectively). Serum CA125 was lower in the prolonged pregnancies (p < 0.05), while CEA and SCC in AF were significantly elevated (p < 0.003 and p < 0.01, respectively). A good correlation was found in CA125 and SCC values between MS and AF (r = 0.43, p < 0.0001; r = 0.32, p < 0.004 respectively), while no correlation was observed between MS and AF CEA values. In conclusion, the presence of considerable CEA, CA125 and SCC levels in amniotic fluid during pregnancy suggests their involvement in biological functions, associated with fetal development and maturation. Maternal serum CEA, in contrast to CA125 and SCC, is not influenced by pregnancy, remaining a reliable tumor marker in monitoring also pregnant cancer patients.
Keywords: CA125; CEA; Delivery; Labor; Oncofetal antigens; Pregnancy; SCC; Tumor-associated antigens